Character-Based Human Resource Management in Islamic Educational Institutions - Toni Nasution; Nurmadiah Nurmadiah; Imet Nur; Syari Riqki Bintania (Thawalib: Jurnal Kependidikan Islam, 2026)
Islamic education human resource management (HRM) generally focuses only on technical administration, neglecting the holistic integration of moral character and prophetic values. Objective: To analyze the concepts, principles, implementation strategies, and challenges of character-based human resource management in Islamic educational institutions. Methodology: A qualitative library research approach utilizing a Systematic Literature Review (SLR) with a PRISMA framework, along with thematic analysis of secondary data from Scopus databases. Results: Analysis of 28 sources indicates that Islamic character-based HRM is highly relevant for enhancing institutional competitiveness. The research is globally mapped, dominated by health and social literature from the Middle East and Asia. The synthesis results confirm that integrating prophetic values, transformative leadership, incentive fairness, and effective employee retention can sustainably strengthen the quality of madrasahs, boarding schools, and Islamic educational institutions. This approach successfully combines modern professionalism with spiritual ethics, creating adaptive, highly integral staffing governance that provides universal benefits for the community. Conclusion: Islamic character-based HRM unites modern competence and prophetic values to realize globally competitive educational institutions. Significance: Provides a theoretical contribution of a prophetic framework and practical guidance for Islamic institution leaders to improve quality.